2004
DOI: 10.1107/s0108768103029136
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrated metal(II) complexes of N-(6-amino-3,4-dihydro-3-methyl-5-nitroso-4-oxopyrimidin-2-yl) derivatives of glycine, glycylglycine, threonine, serine, valine and methionine: a monomeric complex and coordination polymers in one, two and three dimensions linked by hydrogen bonding

Abstract: Nine hydrated complexes of Group 2 (alkaline earth) cations with organic ligands which are N-substituted amino acids containing the 6-amino-3,4-dihydro-3-methyl-5-nitroso-4-oxopyrimidin-2-yl group have been structurally characterized. The octahydrated calcium glycinate complex, where the six-coordinate Ca cation lies on an inversion centre in the space group P\bar 1, forms a finite (zero-dimensional) complex. The hexahydrated barium glycinate complex contains eight-coordinate Ba and it is isostructural with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, the N-amino acid side-chain deviates from this plane. The bond lengths in the pyrimidine group are similar to those of analogous derivatives, [12][13][14] which points to an extensive electronic delocalisation in this moiety. This results in a bipolar character for the pyrimidine with a positive charge located on the NHC(2)N(3)C(4)NH 2 group and a negative one on C(5) NO (Scheme 2).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the N-amino acid side-chain deviates from this plane. The bond lengths in the pyrimidine group are similar to those of analogous derivatives, [12][13][14] which points to an extensive electronic delocalisation in this moiety. This results in a bipolar character for the pyrimidine with a positive charge located on the NHC(2)N(3)C(4)NH 2 group and a negative one on C(5) NO (Scheme 2).…”
Section: Resultsmentioning
confidence: 94%
“…The pyrimidine moiety shows similar structural and electronic features to analogous compounds mentioned above. [12][13][14] The C(5)NO group is oriented trans to C(6) in such a way that its oxygen atom O(5) is able to form an intramolecular N-H···O hydrogen bond in an S(6) motif, which is coplanar with the pyrimidine ring. However, the N-amino acid side-chain deviates from this plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 18 This interaction is driven not only by van der Waals forces but also by a strong polar interaction, 19 arising from the electron-withdrawing π cloud by the exocyclic C(5)-NO group. 20 22 Thus, it is expected that this mechanism is preserved when compounds similar to those of Scheme 1 a but with different substituent R are attached to graphene. This will result in graphene–pyrimidine derivative hybrids having on their surface the R function of the pyrimidine derivative.…”
Section: Introductionmentioning
confidence: 98%
“…We have previously reported that the attachment of C(5)­nitroso-pyrimidine derivatives (Scheme a) onto the surface of some carbon materials takes place by π stacking between the planar pyrimidine-conjugate residue and the arene centers, Cπ, of the graphene surface. This interaction is driven not only by van der Waals forces but also by a strong polar interaction, arising from the electron-withdrawing π cloud by the exocyclic C(5)-NO group. Thus, it is expected that this mechanism is preserved when compounds similar to those of Scheme a but with different substituent R are attached to graphene. This will result in graphene–pyrimidine derivative hybrids having on their surface the R function of the pyrimidine derivative.…”
Section: Introductionmentioning
confidence: 99%